Selected poems of Malcolm Lowry - Lowry, Malcolm 1909-1957 (The pocket poets series, 2017)
"While famous for his celebrated novel, Under the Volcano, Malcolm Lowry always considered himself a poet. First published in 1962 and long out of print, Selected Poems of Malcolm Lowry is the only comprehensive selection of his poetry to be published, and it remains the perfect introduction to his extensive poetic canon. Edited by Lowry's good friend, renowned Canadian poet Earle Birney, with the assistance of his widow, Margerie Lowry, the selection includes extraordinary poems written during Lowry's stay in Mexico, many of which are closely related to his novel. This new edition includes a "Publisher's Note" from Lawrence Ferlinghetti"...